In Vitro Drug Release Studies of Metronidazole Topical Formulations Through Cellulose Membrane (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Three different topical formulations namely gel, cream and ointment, each containing 1% w/w metronidazole, were prepared and in vitro permeation studies carried out. The permeation of metronidazole from each of the topical formulation was determined using dialyzing cellulose membrane in a dissolution tester. Glycerin, a permeation enhancer, was incorporated in varying concentrations and the amount of permeated metronidazole analysed using high performance liquid chromatography. The drug release was found to be greatest in the gel formulation followed by cream and ointment preparations in that order. Incorporation of glycerine enhanced drug release profile.
Keywords: Metronidazole formulation; in vitro studies; permeation; glycerine